2016
DOI: 10.1093/cvr/cvw016
|View full text |Cite
|
Sign up to set email alerts
|

Counteractive effects of omentin-1 against atherogenesis

Abstract: This study provided the first evidence that omentin-1 may serve as a novel therapeutic target for atherosclerosis and CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(180 citation statements)
references
References 47 publications
3
174
0
1
Order By: Relevance
“…With respect to CVD, circulating omentin was decreased in patients with coronary artery disease and appeared to have a protective role in patients with ischaemic stroke . In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation …”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…With respect to CVD, circulating omentin was decreased in patients with coronary artery disease and appeared to have a protective role in patients with ischaemic stroke . In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation …”
Section: Introductionmentioning
confidence: 72%
“…8,9 In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion 10 and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation. 11 In contrast with the findings from cross-sectional and experimental studies, the prospective analysis within the KORA F4/FF4 cohort indicated that higher circulating omentin is associated with a higher risk of T2D. 12 This is in line with a prospective analysis within the European Prospective Investigation into Cancer and Nutrition-Potsdam study demonstrating an increased omentin-related diabetes risk among people with high adiponectin levels.…”
Section: Introductionmentioning
confidence: 83%
“…Consistently, administration of omentin-1 in ApoE-KO mice decreased atherosclerosis. 59 Omentin-1 treatment also enhanced vasodilation in isolated aortic rings of mice in an eNOS-dependent pathway 60 (Figure 3). Omentin-1 enhances endothelial cell differentiation into capillary-like structures, and decreases endothelial cell apoptosis in an AMPK/eNOS-dependent fashion (Figure 3).…”
Section: Omentin-1mentioning
confidence: 92%
“…18 One of the cytokines involved in the endocrine homeostasis of body fat is omentin, which is synthesized by adipocytes in visceral and subcutaneous fat, as well as by endothelial cells. [19][20] Omentin, also known as intelectin 1, is encoded by the ITLN1 gene located on the long arm of chromosome 1 (1q21.3). 21 A study of another allelic variant of the ITLN1 gene, rs1333062, showed the strongest association of the variant in a body mass index--stratified analysis of Indians with T2DM.…”
mentioning
confidence: 99%